Effects of water types and roasting points on consumer liking and emotional responses toward coffee. (October 2022) - Won Kang, Gi; Piao, Zhenxian (Zoey); Youn Ko, Jae
Highlights: Water's significant role in brewing coffee. Consumers' preferred conditions concerning coffee's brewing water. Emotion lexicons for consumers' coffee tasting of nine samples. Impact of water constituents regarding formulation development and processing. Abstract: Although the roles of coffee origin, roasting degree, and consumption methods on the sensory properties of coffee have been actively discussed, the type of water used in brewing plays as important a role as coffee beans, roasting degree, and brewing skills in deciding coffee quality. As water is an essential ingredient in coffee brewing, we must consider its role in the process. This study analyzed the impact of three types of water (depending on total dissolved solids [TDS]) on consumer liking (appearance, flavor, taste, aftertaste, and overall) and coffee emotion lexicons at three roasting degrees (three water types × three roasting points). A total of 167 consumers evaluated their liking for nine coffee samples and conveyed their emotion lexicons utilizing the check-all-that-apply method. For coffee extraction, purified water, tap water, and bottled water from Australia were used for the evaluation and they had TDS content of approximately 0, 100, and 200 ppm, respectively. An analysis of variance demonstrated that all sensory attributes had significant differences, except for aftertaste. Consumer liking decreased in relation to increasing TDS at the medium and dark roasting points. Coffee brewed using purified water was preferred by coffee consumers at medium and dark roasting points. Additionally, when they had their highly preferred coffee samples, they experienced positive emotions, such as feeling energetic, nostalgic, independent, adventurous, and focused.